Sustainable ammonia a key technological challenge for Asia. - Razon, Luis F.
Ammonia is one of the most important industrial chemicals in the world. The availability of an inexpensive and environmentally sustainable supply of ammonia which is an important ingredient in fertilizer is important for the security of the world food supply. Asia is one of the biggest consumers of ammonia. The Haber-Bosch process makes ammonia widely available now but it requires high temperatures and pressures, consumes large quantities of fossil fuels and releases large amounts of greenhouse gases. Sustainable ammonia is also important because it may make biomass-based alternatives to fossil fuels more practical. Possible alternatives under development are those that mimic the enzymatic processes that occur at mild conditions in nature and those that seek to obtain ammonia-based compounds from large-scale culture of microalgae and cyanobacteria. Many of the alternatives are still in the very early stages of development and researchers are urged to enter the field.
Keywords: Ammonia; Fertilizer; Food security; Haber-bosch.; Microalgae; Nitrogen Fixation